Exploring Mentorship as a Novel Approach to Improving Quality of Life in Sarcoma Survivors: A Qualitative Pilot Study. (10th August 2021) - Våde, Lotta; Hompland, Ivar; Fauske, Lena
Abstract : Backgrounds . To investigate whether a formal mentoring program involving mentors from the business community could improve the quality of life (QoL) of sarcoma survivors struggling with the late effects of treatment. Methods . Seven former sarcoma patients participated in an eight-month formal mentoring program. The program was assessed through a qualitative study involving a phenomenological approach that utilized a hermeneutical design. In-depth, semistructured interviews were conducted with the mentees after the intervention and six months later. The mentors were interviewed after the program was over. The gathered data were interpreted using a thematic analysis. Results . The program facilitated dialogue between the mentors and mentees as well as between the mentees. Afterwards, the mentees were more willing to accept the challenges they faced following cancer treatment. During the program, the mentees were pushed out of their comfort zone, which led to mastery and personal growth in them all. However, the program also revealed some additional challenges, including unfulfilled expectations in two mentor-mentee relationships. Conclusions . The mentoring program facilitated the mentees' reorientation and enhanced their QoL. Its eight-month duration appeared important in terms of allowing the mentees to go through a long-lasting process with continued support. The program could serve as the basis for larger studies involving other cancer survivors.